Genetic diversity of selected commercial freshwater fishes based on phospholipase C zeta expression and muscle protein profiling - Norbidin, Noor Azimah (2014)
Egg activation is important to help releases the egg from meiotic arrest and blocks polyspermy. It is linked with an increase in intracellular egg calcium ions (Ca2+) in almost all species studied and current studies imply that the mammalian sperm factor involved is a sperm-specific phospholipase C zeta, PLCζ. Here, we first reported the identification of PLCζ in the testis and egg of Lampam Jawa. Our findings provide the evidence that PLCζ is present in the species of male and female Lampam Jawa (Barbonymus gonionotus). For this study, six types of commercial freshwater fish were selected i.e. Red Tilapia (Oreochromis sp. Red Tilapia), Black Tilapia (Oreochromis mossambicus), Catfish or Keli (Ictalurus punctatus), Silver Catfish or Patin (Pangasius pangasius), Snakehead Fish or Haruan (Channa striata) and Silver Barb or Lampam Jawa (Barbonymus gonionotus). The objectives of this study were to isolate the mRNA from the gonads of freshwater fishes, to identify and amplify the phospholipase C zeta (PLCζ) gene fragments, to sequence the purified DNA fragments and to compare the PLCζ sequence to other PLCζ sequence available in NCBI database, to characterize muscle protein of selected commercial freshwater fish and lastly, to compare phylogenetic trees of 16S rDNA generated. In addition, protein profiles can be used as indicators of evolutionary relatedness. The differences and similarity aspects of fish muscle protein were measured and the relatedness based on protein profile was compared with the relatedness of fishes obtained from 16S rDNA sequences alignment by using dendrogram. The methods used for the expression of PLCζ were RNA extraction, spectrophotometric quantitation of RNA, Two-Step RT-PCR reaction, agarose gel electrophoresis, gel documentation, gel extraction, sequencing and dendrogram. The methods used for muscle protein profiling were sodium dodecyl sulphate polyacrylamide gel electrophoresis (SDSPAGE), gel viewing, muscle’s protein banding profile analysis, genetic diversity and lastly comparison of protein profile and 16S phylogenetic tree generated by using dendrogram. For the study of PLCζ expression, male and female Lampam Jawa showed bands at around 420bp in agarose gel electrophoresis that indicated the presence of PLCζ gene and no significant bands were found in other types of fishes used in this study. For muscle protein profiling, the multiple bands of proteins obtained from SDS – PAGE showed similar protein contents among different fish species used in this study. The dendrogram showed the highest percentage of similarity is between Tilapia Hitam and Tilapia Merah which is 84% followed by Haruan and Patin which exhibited less than 84% similarity. Keli had 67% similarity with Haruan, Patin, Tilapia Merah and Tilapia Hitam while Lampam Jawa showed less than 60% similarity with Keli, Patin, Haruan, Tilapia Merah and Tilapia Hitam.